Dirty Window - Stokman, Walter (Netherlands)
In the night of the 18th of February 2009, 19-year-old prostitute Betty Szabó was murdered in her room in Amsterdam. The film follows the trail back to Betty’s birthplace Nyíregyháza in Hungary, where the contours of her existence slowly start to take shape, as people from her past relay their memories about her.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films